Achieving abiotic stress tolerance in plants through antioxidative defense mechanisms - Mishra, Neelam; Jiang, Chenkai; Chen, Lin; Paul, Abhirup; Chatterjee, Archita; Shen, Guoxin (Frontiers in Plant Science, 2023)
Climate change has increased the overall impact of abiotic stress conditions such as drought, salinity, temperature extremes etc. in plants. Abiotic stress adversely affects the overall growth, development, crop yield and productivity in plants. When plants are subjected to various stressed environmental conditions, balance between the production of reactive oxygen species and its detoxification through antioxidant mechanisms is disturbed. Extent of disturbance depends on the severity, intensity and duration of abiotic stress. Equilibrium between the production and elimination of reactive oxygen species is maintained due to both enzymatic and non-enzymatic antioxidative defense mechanisms. Non enzymatic antioxidants include both lipid soluble (α- tocopherol and β carotene) and water soluble (glutathione, ascorbate etc.) antioxidants while ascorbate peroxidase (APX), superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR) are major enzymatic antioxidants that are essential for ROS homeostasis. In this review, we intend to discuss various antioxidative defense approaches used for improvement of abiotic stress tolerance in plants and the mechanism of action of the genes or enzymes involved in it.